Analysis and Study of the Use of Digital National Identity Card Services in Generation Z - Zahlimar; Abu Bakar; Ipik Permana; Mukarto Siswoyo; Hamirul (HM Publisher, 2023)
One of the latest innovations that has caught the attention of generation Z is the introduction of the digital identity card. As a substitute for physical ID cards that have been around for a long time, digital ID cards offer various benefits and attractive potential for generation Z. In this approach, a digital ID cards are a digital version of a person's identity that is stored electronically, with personal information such as name, address, and number identity. However, a digital ID card is not just a substitute for a physical ID card but a tool that enables generation Z to make wider use of information technology. This study aimed to explore the use of digital national identity cards in generation Z. This research is qualitative research that explores and describes in detail a situation or phenomenon of the research object being researched by developing concepts and gathering existing facts. Raw data is analyzed and organized by data collection date, data source, data type, data description, and data nature. All data must be read in order to find out what data has been obtained, the source of the data, and its meaning. Overall, generation Z has a positive opinion of digital ID card services. They see it as convenience and convenience to access their identity electronically, avoiding the need to carry physical documents all the time and speeding up administrative processes. Generation Z also appreciates the administrative efficiency offered by digital Identity Card services, enabling them to process ID card extensions or personal data changes more easily and quickly. Apart from that, generation Z also appreciates the integration of digital ID card services with other digital platforms. They can integrate their identity with banking services, e-commerce, or online ordering platforms, enabling them to make transactions easily and quickly. Generation Z is also aware of the positive impact of using digital ID cards on the environment by reducing the use of physical documents and contributing to sustainability.